2015
DOI: 10.1523/jneurosci.4442-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of Lysosomal Ca2+Efflux Rescues Abnormal Lysosomal Storage in FIG4-Deficient Cells

Abstract: Loss of function of FIG4 leads to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 46 publications
4
54
1
Order By: Relevance
“…Therefore, PI3,5P 2 deficiency in Fig4 −/− cells would deactivate the TRPML-1 channel and impair lysosomal membrane trafficking. Indeed, our studies have shown increased intralysosomal Ca 2+ and impaired lysosomal fission in Fig4 −/− cells, including myelinating Schwann cells 11 . Lysosomal membrane trafficking has been suggested to be important for myelination 12,13 .…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…Therefore, PI3,5P 2 deficiency in Fig4 −/− cells would deactivate the TRPML-1 channel and impair lysosomal membrane trafficking. Indeed, our studies have shown increased intralysosomal Ca 2+ and impaired lysosomal fission in Fig4 −/− cells, including myelinating Schwann cells 11 . Lysosomal membrane trafficking has been suggested to be important for myelination 12,13 .…”
Section: Introductionmentioning
confidence: 59%
“…Our previous study has shown that abnormal lysosomal storage in FIG4 deficient mouse fibroblasts was mainly caused by a lysosomal fission defect while lysosomal fusion was normal 11 . We verified this mechanism in five patients with CMT4J.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Deficiency of PI(3,5)P 2 results in enlarged endolysosomal vacuoles, possibly generated by osmotic swelling due to impaired activation of the lysosomal cation channels TRPML1 (MIM: 605248), TPCN1 (MIM: 609666), and TPCN2 (MIM: 612163). [10][11][12][13][14] Neurons are particularly sensitive to reduced abundance of PI(3,5)P 2 . 15 Mutations of FIG4 result in recessive neurological disorders, including the peripheral neuropathy Charcot-Marie-Tooth type 4J (MIM: 611228), the multisystem disorder Yunis-Varón syndrome (MIM: 216340), and polymicrogyria with seizures and psychiatric co-morbidities (MIM: 612691).…”
mentioning
confidence: 99%
“…What appears to be a common observation is that TRPML1 plays a role in metal ion homeostasis [21, 28, 31, 64], membrane trafficking [21, 41], and exocytosis of intracellular contents [66, 88] via the endosomal-lysosomal pathway. Recently, the forced induction of TRPML1 channel activity through an agonist or synthetic ligand (ML1-SA) has been shown to rescue phenotypes of various diseased models of Charcot-Marie-Tooth disease Type 4J and human immunodeficiency virus-induced dementia [6, 118]. Thus, the ability of TRPML1 to rescue disease phenotypes involving lysosomes add to a growing evidence of its importance in normal lysosomal physiology.…”
Section: Introductionmentioning
confidence: 99%